STRENGTHENING STUDENTS’ READING LITERACY THROUGH SCHOOL-BASED LITERACY MOVEMENT PROGRAMS IN INDONESIAN JUNIOR SECONDARY SCHOOLS - Martha Khristina Kota; Treesly Yumiardi Normin Adoe (SENSEI RESEARCH CENTER, 2024)
Reading literacy is very important for students, but the reading ability of Indonesian students is still low. The government has made the School Literacy Movement to improve students' reading. This study discusses the strengthening of reading literacy through school-based literacy movement programs. The study used a mixed-method design. The data were collected through a reading test, questionnaire, observation, interview, and journal. The result shows that the reading literacy and reading engagement of the students improved after the program, although there were also some obstacles such as limited books and different reading abilities of the students. The school literacy movement program should be continued and supported by all school members.